High-viscosity polyvinyl chloride paste resin and production process thereof
By adding polymethylphenylsiloxane modified nanosilia-hydrotalcite material to the polyvinyl chloride paste resin, the problems of low viscosity, thermal stability and moisture resistance of the polyvinyl chloride paste resin are solved, and the effects of high viscosity, good thermal stability and moisture resistance are achieved, and the scope of application is expanded.
Patent Information
- Application Number
- CN202510129851.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-25
AI Technical Summary
The existing high viscosity of high-viscosity and foaming polyvinyl chloride paste resin PB1152C is low, resulting in the slurry not being hung on the internet when preparing downstream products, affecting the quality of latex products. In addition, the thermal stability and moisture resistance of the polyvinyl chloride paste resin are poor, limiting its application range.
Nano-silica-hydrotalcite material (PMPS/SiO2-LDH) modified with polymethylphenylsiloxane was added to the polyvinyl chloride paste resin as a heat and humidity resistance. By improving the polymerization reaction and post-treatment process, its viscosity, thermal stability and moisture resistance are improved.
The viscosity, thermal stability and moisture resistance of the polyvinyl chloride paste resin are significantly improved, making it more suitable for the preparation of high-quality downstream products, and expanding its application range.
Smart Images

Figure BDA0005261178510000061 
Figure BDA0005261178510000071
Abstract
Description
Technical Field
[0001] The invention relates to vinyl chloride paste resin, in particular to a high-viscosity polyvinyl chloride paste resin and a production process thereof. Background Art
[0002] Polyvinyl chloride paste resin is a polymer product made from monomer vinyl chloride. It is a conventional chemical raw material and is widely used. In the prior art, the high-viscosity and high-foaming polyvinyl chloride paste resin PB1152C used in the production of downstream products such as latex gloves, anti-slip mats, yoga mats, etc. has low viscosity and has the disadvantages of the slurry not being able to hang on the net when preparing downstream products, which affects the quality of latex products and limits the application scope of polyvinyl chloride paste resin.
[0003] Polyvinyl chloride paste resin is an amorphous polymer with a plasticizing temperature of 140-230℃. Due to the presence of double bonds, branching points and initiator residues in its molecular structure, it is very easy to decompose under the action of heat and oxygen, especially at high temperatures, where the decomposition is aggravated, a large amount of hydrogen chloride is released, the color deepens, and the mechanical properties decrease, which brings great difficulties to processing. In order to maintain processing stability and ensure the quality of products, it is necessary to improve the thermal stability of polyvinyl chloride paste resin.
[0004] The structure of polyvinyl chloride paste resin itself is loose, and there are many gaps in the obtained polyvinyl chloride paste resin for water to penetrate. After absorbing water, the polyvinyl chloride paste resin may have poor fluidity during processing, affecting its molding and processing performance; therefore, its poor moisture resistance problem needs to be improved. Summary of the invention
[0005] The object of the present invention is to provide a high-viscosity polyvinyl chloride paste resin, which has high viscosity, good thermal stability and moisture resistance.
[0006] Another object of the present invention is to provide a production process for high-viscosity polyvinyl chloride paste resin, which has simple operation, convenient operation control, stable quality, high production efficiency, low production cost, and is suitable for large-scale industrial production.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A high-viscosity polyvinyl chloride paste resin comprises the following raw materials in parts by weight:
[0009] 200-220 parts of vinyl chloride monomer, 200-220 parts of deionized water, 2-4 parts of emulsifier, 0.1-0.2 parts of initiator, 3-5 parts of heat and moisture resistant agent, 2-3 parts of post-treatment agent;
[0010] The heat-resistant and moisture-resistant agent is a nano-silica-hydrotalcite material modified by polymethylphenylsiloxane, which is recorded as PMPS / SiO2-LDH.
[0011] Another object of the present invention is achieved by the following technical solution: A production process of high-viscosity polyvinyl chloride paste resin, comprising the following steps:
[0012] S1, uniformly mixing vinyl chloride monomer, deionized water, emulsifier, initiator and heat and moisture resistant agent according to weight, and then putting them into a polymerization reactor for polymerization reaction for 8-10 hours to obtain latex;
[0013] S2, adding a post-treatment agent to the latex, performing a stabilization treatment for 0.5-1h, spray drying, and crushing with a pulverizer to obtain a polyvinyl chloride paste resin.
[0014] Furthermore, the emulsifier described in S1 is one of sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate and sodium lauryl sulfate.
[0015] Furthermore, the initiator described in S1 is one of azobisisobutyronitrile and azobisisobutyronitrile.
[0016] Furthermore, the heat-resistant and moisture-resistant agent in S1 is prepared by the following steps:
[0017] 1) adding hydrotalcite to deionized water and ultrasonically treating it for 0.5-1h to obtain solution 1, adding tetraethyl orthosilicate to anhydrous ethanol and mixing evenly to obtain solution 2, mixing solution 1 and solution 2 at room temperature for reaction for 36-48h to obtain a reaction solution; drying and grinding the reaction solution at 50-60°C to obtain silicon dioxide-hydrotalcite, recorded as SiO2-LDH;
[0018] 2) SiO2-LDH was added to n-butanol, and ultrasonic stirring was performed for 0.5-1 h to obtain a dispersion, and the dispersion was heated to 70-80° C., polymethylphenylsiloxane was added, and the reaction was stirred for 3-4 h, centrifuged, washed with anhydrous ethanol, dried at 60-70° C. for 24 h, and ground to obtain a polymethylphenylsiloxane-modified nano-silica-hydrotalcite material, which was recorded as PMPS / SiO2-LDH.
[0019] Furthermore, in step 1), the mass ratio of hydrotalcite to tetraethyl orthosilicate is 1:0.5-2;
[0020] Hydrotalcite is magnesium aluminum hydrotalcite, in which Mg 2+ and Al 3+ The molar ratio is 3:1.
[0021] Furthermore, in step 2), the mass ratio of SiO2-LDH to polymethylphenylsiloxane is 2:1.
[0022] Furthermore, before the polymerization reaction in S1, the polymerization kettle is subjected to vacuum deoxygenation treatment, and the vacuum degree of the vacuum deoxygenation treatment is -0.05 MPa.
[0023] Furthermore, the post-treatment agent in S2 is one of polyethylene glycol 400 dioleate, polyethylene glycol 600 dioleate and fatty alcohol polyoxyethylene ether.
[0024] Further, the spray drying temperature in S2 is 220-230°C;
[0025] The pulverizer pulverizes the polyvinyl chloride paste resin into a particle size of 0.1-1.5 μm.
[0026] Beneficial effects of the present invention:
[0027] (1) The polymethylphenylsiloxane-modified nano-silica-hydrotalcite material (PMPS / SiO2-LDH) prepared by the present invention is added to the polyvinyl chloride paste resin, so that the polyvinyl chloride paste resin has high viscosity, good thermal stability and moisture resistance.
[0028] (2) PMPS / SiO2-LDH can be evenly dispersed in the polyvinyl chloride paste resin matrix, making the polyvinyl chloride paste resin densely packed inside and reducing the porosity of the polyvinyl chloride paste resin, thereby increasing the viscosity of the polyvinyl chloride paste resin; polyvinyl chloride paste resin will thermally decompose at high temperature to produce HCl gas, which catalyzes the thermal decomposition and can accelerate the thermal decomposition, resulting in poor thermal stability of the polyvinyl chloride paste resin. The alkaline ions in the hydrotalcite in PMPS / SiO2-LDH can well absorb the HCl gas produced by the thermal decomposition of the polyvinyl chloride paste resin and prevent the catalytic effect of HCl on the thermal decomposition of the polyvinyl chloride paste resin, thereby making the polyvinyl chloride paste resin have good thermal stability; polymethylphenylsiloxane gives PMPS / SiO2-LDH good hydrophobicity, thereby making the polyvinyl chloride paste resin have good moisture resistance. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Preparation Example 1
[0031] This preparation example provides a heat and moisture resistant agent, which is prepared by the following steps:
[0032] 1) adding 6 g of hydrotalcite to 50 mL of deionized water and ultrasonically treating the mixture for 0.5 h to obtain solution 1; adding 3 g of ethyl orthosilicate to 50 mL of anhydrous ethanol and mixing the mixture to obtain solution 2; mixing solution 1 and solution 2 and reacting the mixture at room temperature for 48 h to obtain a reaction solution; drying and grinding the reaction solution at 60° C. to obtain silicon dioxide-hydrotalcite, referred to as SiO2-LDH;
[0033] 2) Add 6 g of SiO2-LDH to n-butanol, ultrasonically stir for 0.5 h to obtain a dispersion, heat the dispersion to 70°C, add 3 g of polymethylphenylsiloxane, stir and react for 3 h, centrifuge, wash with anhydrous ethanol, dry at 60°C for 24 h, and grind to obtain a polymethylphenylsiloxane-modified nano-silica-hydrotalcite material, recorded as PMPS / SiO2-LDH-1.
[0034] Preparation Example 2
[0035] Compared with Preparation Example 1, the difference between this Preparation Example is that the "6g hydrotalcite, 3g tetraethyl orthosilicate" in step 1) is changed to "6g hydrotalcite, 6g tetraethyl orthosilicate" to obtain PMPS / SiO2-LDH-2; the remaining raw materials and preparation process remain the same as Preparation Example 1.
[0036] Preparation Example 3
[0037] Compared with Preparation Example 1, the difference between this Preparation Example is that the "6 g hydrotalcite, 3 g tetraethyl orthosilicate" in step 1) is changed to "6 g hydrotalcite, 12 g tetraethyl orthosilicate" to obtain PMPS / SiO2-LDH-3; the remaining raw materials and preparation process remain the same as those in Preparation Example 1.
[0038] Example 1
[0039] This embodiment provides a high-viscosity polyvinyl chloride paste resin, comprising the following raw materials in parts by weight:
[0040] 200 parts of vinyl chloride monomer, 200 parts of deionized water, 2 parts of sodium dodecylbenzene sulfonate, 0.1 parts of azobisisobutyronitrile, 2 parts of polyethylene glycol 400 dioleate, and 13 parts of PMPS / SiO2-LDH-.
[0041] A production process of high-viscosity polyvinyl chloride paste resin comprises the following steps:
[0042] S1, vinyl chloride monomer, deionized water, sodium dodecylbenzene sulfonate, azobisisobutyronitrile and PMPS / SiO2-LDH-1 are uniformly mixed and put into a polymerization reactor, and the polymerization reactor is subjected to vacuum deoxygenation treatment, the vacuum degree of the vacuum deoxygenation treatment is -0.05MPa, and a polymerization reaction is carried out for 10 hours to obtain latex;
[0043] S2. Add polyethylene glycol 400 dioleate to the latex, stabilize it for 1 hour, spray dry it at 230°C, and grind it into a polyvinyl chloride paste resin with a particle size of 0.1-1.5 μm.
[0044] Example 2
[0045] Compared with Example 1, the difference between this example is that "PMPS / SiO2-LDH-13 parts" in the raw materials is changed to "PMPS / SiO2-LDH-14 parts"; the other raw materials and preparation process remain the same as in Example 1.
[0046] Example 3
[0047] Compared with Example 1, the difference between this example is that "PMPS / SiO2-LDH-13 parts" in the raw materials is changed to "PMPS / SiO2-LDH-15 parts"; the other raw materials and preparation process remain the same as in Example 1.
[0048] Example 4
[0049] Compared with Example 3, this embodiment differs in that "PMPS / SiO2-LDH-15 parts" in the raw materials is changed to "PMPS / SiO2-LDH-25 parts"; the remaining raw materials and preparation process remain the same as Example 3.
[0050] Example 5
[0051] Compared with Example 3, this embodiment differs in that "PMPS / SiO2-LDH-15 parts" in the raw materials is changed to "PMPS / SiO2-LDH-35 parts"; the remaining raw materials and preparation process remain the same as Example 3.
[0052] Example 6
[0053] Compared with Example 4, the difference between this example is that "2 parts of polyethylene glycol 400 dioleate" in the raw material is changed to "3 parts of polyethylene glycol 400 dioleate"; the other raw materials and preparation process remain the same as those in Example 4.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 1 is that no heat-resistant and moisture-resistant agent is added; the other raw materials and preparation process remain the same as those in Example 1.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 1 is that the heat-resistant and moisture-resistant agent is replaced by nano-SiO2; the other raw materials and preparation process remain the same as those in Example 1.
[0058] Comparative Example 3
[0059] The difference between this comparative example and Example 1 is that the heat-resistant and moisture-resistant agent is replaced by SiO2-LDH in Preparation Example 1; the remaining raw materials and preparation process remain the same as in Example 1.
[0060] Comparative Example 4
[0061] Compared with Example 1, the difference between this comparative example is that the heat-resistant and moisture-resistant agent is replaced by PMPS / SiO2, and the preparation process is as follows: 6g of nano-SiO2 is added to n-butanol, ultrasonically stirred for 0.5h to obtain a dispersion, the dispersion is heated to 70°C, 3g of polymethylphenylsiloxane is added, stirred for 3h, centrifuged, washed with anhydrous ethanol, dried at 60°C for 24h, and ground to obtain PMPS / SiO2; the remaining raw materials and preparation process remain the same as those in Example 1.
[0062] The viscosity and heat resistance of the polyvinyl chloride paste resins obtained in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 4 were tested according to GB / T15592-2021; Moisture resistance test: the polyvinyl chloride paste resin was stored in a constant humidity chamber at 80% humidity for 4 hours, and then the polyvinyl chloride paste resin was coated on paper to a thickness of 1.0 mm using an applicator, and foamed in an oven at 230°C to prepare a foam board, the foaming property of the prepared foam board was observed, and photos were taken using an optical microscope, the maximum and minimum sizes of the pores were measured, and the ratio of the maximum size / minimum size was calculated, recorded as the uniformity of the pores, which was used to evaluate the moisture resistance of the polyvinyl chloride paste resin; the results are shown in Table 1:
[0063] Table 1
[0064]
[0065]
[0066] As can be seen from Table 2, compared with Example 1-Example 3, the viscosity increases, the thermal decomposition temperature rises, and the uniformity of the pores becomes better, indicating that increasing the amount of heat-resistant and moisture-resistant agent is beneficial to improving the viscosity, heat resistance and moisture resistance of the polyvinyl chloride paste resin. Compared with Example 3-Example 5, it is found that appropriately increasing the proportion of SiO2 in the heat-resistant and moisture-resistant agent is beneficial to improving the viscosity and heat resistance of the polyvinyl chloride paste resin, while excessive amounts are not conducive to improving the viscosity and heat resistance of the polyvinyl chloride paste resin. The reason may be that adding excessive ethyl orthosilicate may cause the generated SiO2 particle size to increase and the particle dispersibility to deteriorate. Compared with Example 4, Example 6 and Example 4 show that increasing the amount of post-treatment agent is beneficial to improving the viscosity, heat resistance and moisture resistance of the polyvinyl chloride paste resin, because the post-treatment agent can improve the stability of the polyvinyl chloride paste resin.
[0067] Compared with Example 1, Comparative Example 1 has a lower viscosity, a lower thermal decomposition temperature, and a poorer uniformity of pores, indicating that the viscosity, heat resistance, and moisture resistance of the polyvinyl chloride paste resin obtained without adding a heat-resistant and moisture-resistant agent are all poor. Compared with Example 1, Comparative Example 2 only adds nano-SiO2, and although the viscosity is improved, the heat resistance and moisture resistance are reduced. Compared with Example 1, Comparative Example 3 does not use polymethylphenylsiloxane to graft SiO2-LDH, and the moisture resistance of the polyvinyl chloride paste resin obtained is poor. Compared with Example 1, Comparative Example 4 does not use hydrotalcite, and the heat resistance of the polyvinyl chloride paste resin obtained is poor.
[0068] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high viscosity polyvinyl chloride paste resin, characterized in that: The invention comprises the following raw materials in parts by weight: 200-220 parts of vinyl chloride monomer, 200-220 parts of deionized water, 2-4 parts of emulsifier, 0.1-0.2 parts of initiator, 3-5 parts of heat and moisture resistant agent, 2-3 parts of post-treatment agent; The heat-resistant and moisture-resistant agent is a nano-silicon dioxide-hydrotalcite material modified by polymethylphenylsiloxane, which is recorded as PMPS / SiO2-LDH.
2. A production process for high-viscosity polyvinyl chloride paste resin, characterized in that: The steps include: S1, uniformly mixing vinyl chloride monomer, deionized water, emulsifier, initiator and heat and moisture resistant agent according to weight, and then putting them into a polymerization reactor for polymerization reaction for 8-10 hours to obtain latex; S2, adding a post-treatment agent to the latex for stabilization treatment for 0.5-1h, spray drying, and crushing with a pulverizer to obtain a polyvinyl chloride paste resin.
3. The production process of a high-viscosity polyvinyl chloride paste resin according to claim 2, characterized in that: The emulsifier described in S1 is one of sodium dodecylbenzene sulfonate, sodium tetradecylbenzene sulfonate and sodium lauryl sulfate.
4. The production process of a high-viscosity polyvinyl chloride paste resin according to claim 2, characterized in that: The initiator described in S1 is one of azobisisobutyronitrile and azobisisobutyronitrile.
5. The production process of a high-viscosity polyvinyl chloride paste resin according to claim 2, characterized in that: The heat and moisture resistant agent described in S1 is prepared by the following steps: 1) adding hydrotalcite to deionized water and ultrasonically treating it for 0.5-1h to obtain solution 1, adding tetraethyl orthosilicate to anhydrous ethanol and mixing evenly to obtain solution 2, mixing solution 1 and solution 2 at room temperature for reaction for 36-48h to obtain a reaction solution; drying and grinding the reaction solution at 50-60°C to obtain silicon dioxide-hydrotalcite, recorded as SiO2-LDH; 2) SiO2-LDH was added to n-butanol, and ultrasonic stirring was performed for 0.5-1 h to obtain a dispersion, and the dispersion was heated to 70-80° C., polymethylphenylsiloxane was added, and the reaction was stirred for 3-4 h, centrifuged, washed with anhydrous ethanol, dried at 60-70° C. for 24 h, and ground to obtain a polymethylphenylsiloxane-modified nano-silica-hydrotalcite material, which was recorded as PMPS / SiO2-LDH.
6. The production process of a high-viscosity polyvinyl chloride paste resin according to claim 5, characterized in that: In step 1), the mass ratio of hydrotalcite to tetraethyl orthosilicate is 1:0.5-2; Hydrotalcite is magnesium aluminum hydrotalcite, in which Mg 2+ and Al 3+ The molar ratio is 3:
1.
7. The production process of a high-viscosity polyvinyl chloride paste resin according to claim 5, characterized in that: In step 2), the mass ratio of SiO2-LDH to polymethylphenylsiloxane is 2:
1.
8. The production process of a high-viscosity polyvinyl chloride paste resin according to claim 2, characterized in that: Before the polymerization reaction in S1, the polymerization kettle is subjected to vacuum deoxygenation treatment, and the vacuum degree of the vacuum deoxygenation treatment is -0.05 MPa.
9. The production process of a high-viscosity polyvinyl chloride paste resin according to claim 2, characterized in that: The post-treatment agent in S2 is one of polyethylene glycol 400 dioleate, polyethylene glycol 600 dioleate and fatty alcohol polyoxyethylene ether.
10. The production process of a high-viscosity polyvinyl chloride paste resin according to claim 2, characterized in that: The spray drying temperature in S2 is 220-230°C; The pulverizer pulverizes the polyvinyl chloride paste resin into a particle size of 0.1-1.5 μm.